2015
DOI: 10.22436/jmcs.014.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Software Trustworthy Testing Based On Cloud Testing

Abstract: Testing becomes an important process in software development not only in terms of exposure but also in terms of performance, usability, safety, security, reusability. Also software testing is an essential activity to software quality assurance. Cloud testing is a method of software testing based on cloud computing that offers testing as a service To test the SaaS, NonSaaS, service application over clouds and clouds. To test the cloud-based software and applications, tools and techniques are needed to address c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Bandara et al [13], M. Hilty et al [14], H.Q Abdullah et al [16],V. Lelli Dantas et al [15], D. Sahu et al [19], A. Mohsenzadeh et al [20].To completely understand the user requirement is the important step in the development of mobile cloud computing systems which are described by K.AKamaruddin et al [18],M.Hilty et al [14],V.Florio et al [8], F Lins1 [7] Testing is an obvious step that needs to be implemented after a mobile clouding application. Research have shown that a testing can be incremental, which means that after development of every chunk,we have to test the phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bandara et al [13], M. Hilty et al [14], H.Q Abdullah et al [16],V. Lelli Dantas et al [15], D. Sahu et al [19], A. Mohsenzadeh et al [20].To completely understand the user requirement is the important step in the development of mobile cloud computing systems which are described by K.AKamaruddin et al [18],M.Hilty et al [14],V.Florio et al [8], F Lins1 [7] Testing is an obvious step that needs to be implemented after a mobile clouding application. Research have shown that a testing can be incremental, which means that after development of every chunk,we have to test the phase.…”
Section: Discussionmentioning
confidence: 99%
“…Research have shown that a testing can be incremental, which means that after development of every chunk,we have to test the phase. Its importance is reflected in A. Mohsenzadeh et al [20], V. Lelli Dantas [15], D. Kovachev et al [2], L. Murugesan [10], Yonggang Wen et al [6],Performance of a mobile related applications can be improved day by day using different models and techniques that will lead the mobile computing to a much higher level.Many researches have been done for this purpose such as described in N. [18].The great benefit of cloud computing is to transfer a data easily over a wireless medium that gives the attribute of mobility to it and has been discussed by Y. Wen et al [6] ,F. Lins et al [17], D. Sahu et al [19], A. Mohsenzadeh et al [20], C. Shravanthi et al [17].The priority of the paremeters included in table 1 may varies depending upon the scenario in which that application is going to run for example if a device is doing a wireless communication ,mobility parameter will have the higher priority than the device which is just storing the data over the data cloud.Flexibility is a factor that can be defined as elasticity in proving better services in order to accommodate users.Surveying different papers,it has been analyzed that some of the papers discusses the issue of flexibility such as in N.Fernando et al [1],D.Kovachev et al [2], Shih-Hao Chang et al [5],Lins1 et al [7], K.Pousttchi et al [9], L.Murugesan et al [10],S.Abolfazli et al [12],A.KBamdra et al [13],V.Lelli Dantaset al [15],K.AKamaruddin [18],A. Mohsenzadeh et al [20]..Researches have been done to reduce flaws in the the previous systems.…”
Section: Discussionmentioning
confidence: 99%